Renaissance of actor model application to the development of parallel and distributed systems - Glybovets, M.M.; Gorochovskiy, S.S.; Zinchuk, S.O.; Kravchenko, M.V. (PROBLEMS IN PROGRAMMING, 2017)
The article presents the analysis of the Actor model as the high-level approach to architecting parallel and distributed systems. The influence of the object-oriented programming paradigm on the model development as well as key properties of actors are investigated. Finally, the main implementation traits of the Actor model caused by the Scala object-functional language and Akka framework are presented.